How to maintain and keep low and stable inflation in Argentina - Lupan, Alexandru (2016)
This study is titled <How to maintain and keep low and stable inflation in Argentina> and its main purpose is to evaluate possible solutions to the inflation crisis in Argentina. The work will specifically look at the monetary history of Argentina until the most recent days, then it will examine causes of Argentinian inflation and present possible solutions to it. Finally, it examines them and come up with the best theoretical plan.